On spider families (Arachnida: Araneae) new to Armenia - Zarikian Noushig A; Propistsova Evgenia A; Marusik Yuri M (Entomological Society of Israel, 2025)
In this paper, 11 families (Agelenidae, Filistatidae, Hahniidae, Liocranidae, Mimetidae, Mysmenidae,
Oecobiidae, Pholcidae, Phrurolithidae, Sparassidae and Uloboridae), 18 genera and 18 species of spiders new to Armenia are reported. One genus, Mesiotelus Simon, 1897 (Liocranidae) is new to the entire Caucasus. Illustrations are provided for six species.
KEYWORDS: Aranei, spiders, Caucasus, Palaearctic, new records